2004
DOI: 10.1136/bjo.2003.034884
|View full text |Cite
|
Sign up to set email alerts
|

Retinal blood flow measurements and neuroretinal rim damage in glaucoma

Abstract: Aim: To assess retinal blood flow characteristics in subjects with normal tension glaucoma (NTG), primary open angle glaucoma (POAG), and a group of controls using the Heidelberg retina flowmeter (HRF). The vascular parameters were correlated against structural damage of the optic nerve head, assessed using the Heidelberg retina tomograph (HRT). Methods: HRF images were obtained in 76 subjects with NTG, 58 with POAG, and 38 controls. Optic nerve head images, acquired using the HRT, were analysed with Moorfield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 21 publications
3
44
0
7
Order By: Relevance
“…Similar findings have been reported in exfoliative glaucoma in that decreased neuroretinal rim area was found to be correlated with decreased blood flow to the lamina cribrosa and rim, but not the peripapillary retina [120]. However, it has been shown that neuroretinal rim damage is associated with local blood flow reduction in OAG patients [121]. Abnormalities in ONH morphology were shown to be localized to quadrants that corresponded to lower blood flow.…”
Section: Onh Morphologic Changessupporting
confidence: 61%
“…Similar findings have been reported in exfoliative glaucoma in that decreased neuroretinal rim area was found to be correlated with decreased blood flow to the lamina cribrosa and rim, but not the peripapillary retina [120]. However, it has been shown that neuroretinal rim damage is associated with local blood flow reduction in OAG patients [121]. Abnormalities in ONH morphology were shown to be localized to quadrants that corresponded to lower blood flow.…”
Section: Onh Morphologic Changessupporting
confidence: 61%
“…Several clinical investigators [23,24,25] have revealed that both optic disk rim blood flow and peripapillary retinal blood flow are significantly lower in patients with OAG as compared with age-matched controls, and thus optic disk rim blood flow is significantly correlated with deterioration of existing visual field defects. Hafez et al [26] evaluated and compared optic disk rim blood flow in patients with OAG and those with ocular hypertension (OH) and found that OAG patients had significantly lower values than OH patients.…”
Section: Discussionmentioning
confidence: 99%
“…These losses have been related to larger cup-to-disc ratios, 166 and are spatially associated with optic nerve head structural damage and visual field defects. 167,168 Specifically, Logan et al 167 found decreased capillary flow in areas of the retina associated with abnormal optic disc segments. In contrast, normal optic disc segments from these same glaucoma patients were not associated with compromised retinal flow.…”
Section: Relationship Between Ocular Blood Flowvisual Function and mentioning
confidence: 98%
“…These losses have been related to larger cup-to-disc ratios, 166 and are spatially associated with optic nerve head structural damage and visual field defects. 167,168 Combined with the previous technologies' data on retinal blood flow, HRF measurements point to a reduction in retinal blood supply in ophthalmic disease such as glaucomatous optic neuropathy.…”
Section: Confocal Scanning Laser Doppler Flowmetrymentioning
confidence: 99%